Microscopía electrónica de barrido del aparato bucal de larva de Hyla pulchella pulchella (Anura: hilydae) - Echeverría, Dinorah Diana (1992)
Scanning electron microscopy shows that the buccal apparatus of Hyla pulchella pulchella larvae has a well developed and queratinized horny beack with teeth with a main cuspid. Rostrodont with heterodiontial size. Multicusped labial teeth with 10 to 12 (Mo=10) denticles in each paddle; paddle with a short neck, slightly marked. Tipic dental formulae 1,1-1/1-1,2 and 1,1-1/3 have heen observed at any of the development stages with functional teeth. Oval disc with a row of marginal papilae, and a dorsal gap. Submarginal papilae are absent. Queratodonts morfological variations might go on increasing as they make older.